Establishing a two-way transaction pricing model of "platform-individual" co-creation data property rights - Junfeng Liao; Rundong Li (Journal of Innovation & Knowledge (JIK), 2023)
In recent years, the data trading industry has thrived on data assetization. However, given the increasing privacy concerns of the main data providers-individual users-their willingness to disclose data is in decline. Meanwhile, enterprises may violate privacy laws by profiting from co-creation data without user permission, blocking a significant amount of co-creation data from full circulation. This study establishes the utility function of users under three choices-purchase, sale, and maintaining the status quo-that quantify the privacy calculus mechanism and introduce privacy-related variables, employing references and interviews with Tencent employees and users. Accordingly, examining the decision-making behavior of users helped establish a data property rights two-way transaction model comprising six scenarios and, hence, six corresponding platform decisions. Indeed, the model can solve the noted dilemma and realize a Pareto improvement of the utilities of the platform and users. This study contributes a new perspective, constructs a data property rights two-way transaction model, expands the pricing theory boundary, and provides a decision reference for data trading practice, allowing enterprises to establish new business models.
Keywords: P14; P48; R32; 650; Data assetization; Co-creation data; Data pricing; Privacy concerns; Utility function; Value co-creation